The first report on brain sagging dementia caused by a cranial leak: A case report - Lashkarivand, Aslan; Eide, Per Kristian (Frontiers in Neurology, 2022)
Objective Brain Sagging Dementia (BSD) is an increasingly recognized syndrome for which diagnostic criteria recently were proposed. There have been no reports on BSD caused by a cranial leak. Here we present the first report on a patient with BSD caused by a cranial leak. Case description A 60-year old male patient was admitted with a 2-year history of orthostatic headache and gradually progressive cognitive and behavioral changes. Traditional treatments for spontaneous intracranial hypotension, including repeated epidural blood patches, failed. Brain imaging showed severe brain sagging, and intracranial pressure monitoring demonstrated intracranial hypotension. No leakage site was found. His past medical history revealed an accident where a ski pole struck his head at age ten. Due to progressive clinical decline, surgery was pursued. A cranial defect with an accompanying cerebrospinal fluid leak site representing the trauma from his childhood was found and repaired. He also was in need of a ventriculoperitoneal shunt. Following surgery, he improved and recovered completely. Discussion This case report illustrates that a cranial leak may cause BSD, even with a “lucid interval” between trauma and symptom debut spanning many years. Moreover, this report validates well the recently proposed BSD diagnostic criteria.